Analisis Derajat Kerusakan dan Penurunan Modulus Elastisitas Material Cement Treated Base (CTB) menggunakan UPV test dan Concrete Quality Designation (CQD) - Ade Trias Safrudin; Suprapto Siswosukarto; Bambang Suhendro (Jurnal Aplikasi Teknik Sipil, 2023)
Cement-treated base (CTB) is a type of foundation material commonly used in pavement structures which initially has high stiffness, but due to repeated loads CTB tends to experience more cracks which can cause a decrease in its elastic modulus. This study aims to determine the extent of damage and decrease in the value of CTB's elastic modulus before and after cracking through ultrasonic pulse velocity (UPV) test and unconfined compressive strength (UCS) tests on CTB cylinder samples. The CTB material quality index was evaluated using a concrete quality designation (CQD). The results showed that the magnitude of stress applied to  CTB affects the degree of damage, and the degree of damage to CTB significantly affects the material’s modulus of elasticity. The greater the degree of damage to CTB, the smaller the elastic modulus will be. For applied stress with CTB damage level of 32%, the elastic modulus decreases by 33.55%. The level of damage caused by the application of the maximum stress (100%) on CTB sample reached 95.29%, and the modulus of elasticity decreased by 83.30%. The CTB sample with 95.29% degree of damage has the same elastic modulus as the unbound granular aggregate material.